(3OQGSI GdLOhi GdEbJUGOjI hJbjje GdeTQhYGJ (B/s - (3GdUjQaj, eMeO YHO GdaJGMs ((3YeGf(B: s (3OGQ GdacQ ddWHGYI hGdfTQ hGdJhRjY(B, s, 2002)
(3eaGgje CSGSjI, GdOQGSI GdHjFjI, GdOQGSI GdbGfhfjI, GdOQGSI GdafjI ddeTQhY, GdOQGSI GdEOGQjI, GdOQGSI GdJLGQjI, GdOQGSI GdeGdjI, GdOQGSI GdEbJUGOjI, JbQjQ OQGSI GdLOhi, OQGSGJ hMGdGJ JWHjbjIs
Keywords: (3GdeTQhYGJs; (3Jbjje GdCOGAs; (3OQGSI GdLOhis